Real-world TRAE association between niraparib and platinum-based chemotherapy - Wang, Linli; Zhou, Jieli; Wang, Haibin; Han, Wenling; Fang, Chunyun (Frontiers in Oncology, 2024)
Background Pre-clinical studies showed the anti-tumor mechanisms of PARP inhibitors (PARPi) and platinum have some crossover and overlap in the DNA damage repair pathway, patients who respond to platinum-based chemotherapy are also more likely to be sensitive to PARPi. This real-world study mainly aimed to evaluate whether TRAE (treatment-related adverse event) between platinum based chemotherapy (PBC) and niraparib are also associated. Methods Patients received niraparib as maintenance treatment or salvage therapy for advanced ovarian cancer at the First Affiliated Hospital of Gannan Medical University from January 2020 to August 2023 were included. Survival data of niraparib treatment and adverse events occurred during the last platinum-based chemotherapy cycle before starting niraparib treatment and during niraparib treatment are documented. Fisher’s exact test were used for correlation analysis. Results 1. 40 patients treated with niraparib were included in the analysis, including 31 patients treated with niraparib for 1st-line maintenance therapy, 6 patients for PSR (platinum-sensitive recurrence) maintenance therapy, and 3 patients for salvage therapy. The overall median follow-up time was 15.0 months (ranged from 2.2 months to 32.1 months). 2. Overall grade≥3 TRAE (40% vs 70%, p=0.012) including anemia (20% vs 45%, p=0.041) and neutrophil count decreased (17.5% vs 57.5%, p<0.001) was significantly lower during niraparib treatment compared to during chemotherapy. 3. Any grade TRAE (75% vs 100%, p=0.002) including white blood cell count decreased (47.5% vs 87.5%, p<0.001), red blood cell count decreased (57.5% vs 92.5%, p<0.001), anemia (55% vs 87.5%, p<0.001) and neutrophil count decreased (35% vs 85%, p<0.001) were also significantly lower in niraparib treatment group compared with chemotherapy group. No new safety signals were identified. Conclusion 1. In this real-world practice, we observed that patients with advanced ovarian cancer who experienced any grade and grade ≥3 TRAE during chemotherapy were well tolerated when treated with niraparib, particularly the incidence of any grade and grade ≥3 anemia, and neutrophil count decreased during niraparib treatment were significantly lower compared with that during chemotherapy. 2. For patients with ovarian cancer who have experienced grade ≥3 hematological adverse reactions during prior platinum-based chemotherapy, greater attention should be paid to the monitoring and management of hematological adverse reactions during subsequent treatment with niraparib.